2006
DOI: 10.1111/j.1574-6968.1997.tb10263.x
|View full text |Cite
|
Sign up to set email alerts
|

The CS6 colonization factor of human enterotoxigenic Escherichia coli contains two heterologous major subunits

Abstract: The genes encoding the CS6 colonization factor were cloned from two human enterotoxigenic Escherichia coli strains of different serotypes. The DNA sequences from both clones were nearly identical and contained four open reading frames. Two of them have homology to genes encoding molecular chaperones and ushers found in many other operons encoding colonization factors. The two remaining open reading frames encode two heterologous major subunit proteins which makes CS6 unique because other colonization factors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…The Hly plasmids belonged to different incompatibility groups, which suggested that IS91 was involved in the dissemination of these pathogenicity determinants (21,37,53,114). IS91 or very closely related isoforms have also been found adjacent to various other virulence genes in enteropathogenic, enterohemolytic, and enterotoxigenic strains of E. coli (16,42,109), including the eltAB toxin-encoding genes of the heat-labile enterotoxin (89). Furthermore, direct movement of eltAB genes by IS91 has been demonstrated (89).…”
Section: Is91 and Virulence Factorsmentioning
confidence: 99%
“…The Hly plasmids belonged to different incompatibility groups, which suggested that IS91 was involved in the dissemination of these pathogenicity determinants (21,37,53,114). IS91 or very closely related isoforms have also been found adjacent to various other virulence genes in enteropathogenic, enterohemolytic, and enterotoxigenic strains of E. coli (16,42,109), including the eltAB toxin-encoding genes of the heat-labile enterotoxin (89). Furthermore, direct movement of eltAB genes by IS91 has been demonstrated (89).…”
Section: Is91 and Virulence Factorsmentioning
confidence: 99%
“…Representatives of the ␥ 3 -fimbrial clade include AfaC-3, AfaC-7, AfaC-8, AggC, Agg3C, CS3-2, CssD, DraC, and HdaC of E. coli (32,39,76,105,158,187,189,190,238,239,293,361,363,366) (199,254,370) (Fig. 5).…”
Section: The ␥-Fimbriaementioning
confidence: 99%
“…The css operon encodes the CS6 antigen of human enterotoxigenic E. coli, which is present on the cell surface but has a morphology that is beyond the limits of resolution by electron microscopy (205,361). The css operon contains two major subunit genes, and the encoded proteins (CssA and CssB) are present at a 3:1 ratio on the bacterial surface (363,366). The assembly of this surface structure results in the binding of E. coli to human enterocytes (132).…”
Section: The ␥-Fimbriaementioning
confidence: 99%
“…CssC and CssD proteins, encoded by the same gene cluster cssABCD, play the role of chaperone and usher proteins, respectively, and facilitate the assembly and translocation of structural subunits to the bacterial surface (Wolf et al, 1997;Tobias et al, 2008;Wajima et al, 2011). These structural subunits are synthesized from a precursor polypeptide and transferred into the periplasm, where CssA forms a complex with CssB and CssC that is finally recognized by CssD (Tobias et al, 2008;Wajima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CS6 is a hetero-dimeric protein and is composed of two subunits, CssA and CssB, in equal stoichiometry (Wolf et al, 1997;Ghosal et al, 2009). CssC and CssD proteins, encoded by the same gene cluster cssABCD, play the role of chaperone and usher proteins, respectively, and facilitate the assembly and translocation of structural subunits to the bacterial surface (Wolf et al, 1997;Tobias et al, 2008;Wajima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%